FAKTOR-FAKTOR RISIKO PAPARAN Pb PADA POLISI LALU LINTAS DI SEMARANG BARAT - Eni Mahawati (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Background: Based on interview data from 15 traffic police in West Semarang was known that 80% of them have â€œdizzyâ€ and â€œdispneaâ€, 20% have â€œnauseaâ€. Those symptom can be early effect indicator of Pb exposure to them. The aim of this research is to examine Pb Exposure and the risk factors of Pb exposure in traffic police in West Semarang.Method: This is an explanatory research with the cross sectional approach. The respondent in this research is 33 traffic police. Data collected use the direct interview with questioner and laboratory test from the repondentâ€™s blood sample. The variable in this research consist of age, work period, nutrition status, smoking habit, exercise habit, use of mask and Pb concentration in blood.Result: Based on the result of this research was known that the respondent characteristicâ€™s are the mean of their age is 31 years old, work period is 3,77 year, 45,4% have normal nutrition status, 57,6% didnâ€™t use mask, and 37,5% have smoking habit. The average of 8 cigarette smoked a day. The concentration of Pb in blood is 52,18 Î¼g/ml and 60,6% over than threshold limit value. The Result of rank spearman correlation show that there was significant correlation between age and the exercise habit with the Pbconcentration in blood, Ã±-value is smaller than 0,05. Suggestion for Police department is should be applied the health inspection for traffic police and improve the exercise habit for them. Police Placement as traffic police and their mutation must be consider the age of themKeyword : Pb Concentration in blood, Traffic Police